Cotton, Rum, and Reason : Anti-Imperialist Poetry from 19th Century U.S. Newspapers and Post-Colonial Discourse - James, Joshua Nicholas (East Carolina University, 2013)
Though American post-colonial criticism is by no means a field in need of literary material, one particular corpus is missing from the discussion. This thesis situates 19th century anti-imperialist poetry within the larger post-colonial conversation. The poetry that forms the core of this thesis is derived from the front pages of American newspapers as it appeared during three vital stages in the development of the American imperial mindset: the Mexican-American War, the overthrow and annexation of Hawai'i, and the Philippine-American War.   The 19th century poetry featured in this thesis represents an often overlooked voice in post-colonial discourse. The poets are voices of conscience and/or caution that were ultimately drowned out by the power of American expansionism, and these poets have the potential to better illuminate the nature of American empire. Anti-imperialist poetry regarding each of these periods is examined in the thesis from the view of historical context as well as contemporary criticism and poetry indigenous to the three regions mentioned. Period pro-imperialist poetry is also employed to balance the discussion of the emergence of an empire that was, at the time, far from a foregone conclusion.  In this thesis, the voices of post-colonial modernity and 19th century anti-imperialism share the same space and form a broader picture of the impact of American empire building.
Keywords: Literature; Hawaii; Imperialism; Mexico; Philippines; Poetry; Postcolonial; Criticism--United States--19th century; American poetry--19th century; Discourse analysis, Literary--United States; Protest poetry, American--19th century; Political poetry, American--19th century; Patriotic poetry, American--19th century; Postcolonialism in literature; Imperialism in literature